Super-hydrophilic antifouling paint and preparation method thereof

By using different sizes of hydrophilic particles and cellulose to form microconvex and convex surfaces in superhydrophilic coatings, the problems of complex preparation of existing coatings and uneven dispersion of nanotitanium dioxide are solved, and efficient self-cleaning and anti-fouling effects are achieved.

CN119264762AActive Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310813181.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-07
Estimated Expiration
2043-07-05

AI Technical Summary

Technical Problem

The existing ultra-hydrophilic coatings are complex in preparation, have low mechanical properties, thin coatings, and uneven dispersion of nanotitanium dioxide in the polymer, affecting self-cleaning ability and stain resistance.

Method used

Hydrophilic particles of different sizes are connected by coupling agent, combined with aqueous resin and cellulose, forming a microconcave and convex rough surface, improving the hydrophilicity and antifouling properties of the coating.

Benefits of technology

A simple coating preparation process is realized, suitable for large-scale production, the coating has good hydrophilicity and stain resistance, and can achieve self-cleaning function through rainfall to prevent pollutants from adhering.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a super-hydrophilic antifouling coating and a preparation method thereof. The coating is prepared from the following components in parts by weight: 15 to 30 parts of hydrophilic micron particles and hydrophilic nano particles; 20 to 40 parts of hydrophilic resin; 5 to 15 parts of a coupling agent; 1-8 parts of a coalescing agent; and 20 to 50 parts of deionized water. The super-hydrophilic coating is combined with hydrophilic particles with different sizes, nanoparticles with different sizes are effectively and tightly connected through a proper coupling agent, and water-based resin is selected to be matched with a curing agent, so that the particles with different sizes are uniformly dispersed in the resin; then a film-shaped structure containing micron and nano particles is obtained by adding various celluloses, a specific microscopic concave-convex rough surface is formed on the surface of the coating, the affinity between the coating and water is increased, the contact between the surface of the coating and dirt is isolated, and thus a good antifouling effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating preparation, in particular to an antifouling coating with super-hydrophilic properties and a preparation method thereof. Background Art

[0002] After coating, the paint is easily polluted by oily substances in the use environment. There are a lot of soot, kerosene or acidic substances and a lot of exhaust emissions in the atmosphere. When the paint is polluted by the above organic matter, it will lose its decorative color, turn black or gray, or form various yellow spots, affecting its appearance. Taking petrochemical storage tanks as an example, the floating rust formed in the spray water system is easily brought out and attached to the outer wall of the storage tank during the spray water cooling process of the storage tank, forming yellow streaks from top to bottom along the water flow direction, which seriously affects the appearance of the storage tank. Long-term accumulation will also affect the anti-corrosion performance of the coating. This type of pollutant is easy to adhere to the hydrophobic surface, but it is not firmly attached to the hydrophilic surface, and it is also very easy to remove under the scouring of rainwater. Therefore, the hydrophilic self-cleaning theory came into being, and the coating industry also proposed the view that hydrophilic coatings are more resistant to stains than hydrophobic coatings. Hydrophilic coatings make it easy for rainwater to soak its surface, which can not only avoid the water mark problem caused by precipitation but also wash away the dust adhering to the surface of the material. The water film slides down under the action of gravity and carries away the stains, achieving a self-cleaning effect.

[0003] At present, there are two main methods for preparing super-hydrophilic coatings: one is to directly use hydrophilic substances or introduce hydrophilic groups through physical addition or chemical grafting to make the material hydrophilic; the other is to use anatase-type titanium dioxide and organic coatings to synthesize hybrid materials and obtain a super-hydrophilic surface under ultraviolet irradiation. The photocatalytic properties of titanium dioxide can produce strongly oxidizing groups under ultraviolet irradiation, which degrades organic matter into inorganic matter. The photoinduced super-hydrophilicity of nano-titanium dioxide will form hydrophilic groups on the surface of the substrate under ultraviolet irradiation, thereby forming a layer of water film on the surface of the material.

[0004] The patent with publication number CN110093050A, "Super-hydrophilic self-cleaning coating composition, super-hydrophilic self-cleaning glass and its preparation method", introduces a super-hydrophilic self-cleaning coating composition containing modified nano-silica sol, anatase nano-titanium dioxide sol and water. The patent with publication number CN103819989A introduces a super-hydrophilic coating composed of hydrophilic resin, pH regulator, hydrophilic nano-Al2O3, 50% aqueous titanium dioxide slurry, etc. The patent with publication number CN109825156A, "Super-hydrophilic coating and its preparation method, super-hydrophilic coating prepared therefrom and its application", introduces the preparation of a super-hydrophilic coating obtained by mixing a self-crosslinking modified acrylate emulsion with a nano-silica aqueous dispersion and an emulsifier. The patent with publication number CN106380981A, "A modified nano-titanium dioxide self-cleaning coating and its preparation method", introduces a self-cleaning coating mixed with boron-nitrogen doped and coated nano-titanium dioxide, acrylate monomer and co-emulsifier.

[0005] In current research, the preparation methods of super-hydrophilic materials include vapor deposition, self-assembly, plasma treatment, magnetron sputtering, etc., which have problems such as complex operation procedures, low mechanical properties, expensive preparation equipment, and thin coatings. In addition, the single addition of nano-titanium dioxide, due to its large specific surface area, high surface energy, hydrophilic and oleophobic surface, is very easy to agglomerate in the polymer, reducing the photocatalytic activity of the titanium dioxide film. The dispersion of nano-titanium dioxide in the coating is not uniform, which in turn affects the self-cleaning ability and anti-fouling effect. At the same time, the selection and addition of appropriate film-forming aids also have an important influence on the hydrophilic and anti-fouling properties of the coating. Summary of the invention

[0006] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to provide a super-hydrophilic antifouling coating and a preparation method thereof. The super-hydrophilic coating provided by the present invention combines hydrophilic particles of different sizes, effectively and tightly connects nanoparticles of different sizes through appropriate coupling agents, selects water-based resins and curing agents to make particles of different sizes uniformly dispersed in the resin, and then achieves a film-like structure containing micron and nanoparticles by adding a variety of celluloses, forms a specific microscopic concave-convex rough surface on the coating surface, increases affinity with water, isolates the contact between the coating surface and dirt, and thus achieves a good antifouling effect.

[0007] In order to solve the above technical problems, the first aspect of the present invention provides a super hydrophilic coating.

[0008] A super hydrophilic antifouling coating, comprising the following components in parts by weight: Hydrophilic micron particles and hydrophilic nanoparticles, 15-30 parts; Hydrophilic resin, 20-40 parts; Coupling agent, 5-15 parts; Film-forming aid, 1-8 parts; Deionized water, 20-50 parts.

[0009] Furthermore, the hydrophilic micron particles include silicon dioxide and titanium dioxide particles, and the hydrophilic nanoparticles include nano-sized silicon dioxide and titanium dioxide particles; or the hydrophilic micron particles and hydrophilic nanoparticles are selected from silicon dioxide particles coated with titanium dioxide. The particle size of the micron-sized particles is generally 1-10 μm, and the particle size of the nano-sized particles is generally 10-40 nm.

[0010] Furthermore, the hydrophilic resin is epoxy resin or fluorocarbon resin.

[0011] Furthermore, the coupling agent is one or more of tetramethoxysilane, tetraethoxysilane and tetrapropoxysilane.

[0012] Furthermore, the film-forming aid is one or more of carboxymethyl cellulose and hydroxyethyl cellulose, hydroxypropyl cellulose and hydroxypropyl methyl cellulose. Preferably, the film-forming aid is selected from a combination of carboxymethyl cellulose and one or more of hydroxyethyl cellulose, hydroxypropyl cellulose and hydroxypropyl methyl cellulose.

[0013] Furthermore, the weight ratio of the hydrophilic micron particles to the hydrophilic nanoparticles is 1.2-2: 1. When both the micron particles and the nanoparticles are titanium dioxide and silicon dioxide, the total weight ratio of titanium dioxide and silicon dioxide is 0.9-1.1: 1. The amount of the micron-sized silicon dioxide-coated titanium dioxide particles added is 1.2-2 times the amount of the nano-sized silicon dioxide-coated titanium dioxide particles added.

[0014] Furthermore, the silicon dioxide-coated modified titanium dioxide can be prepared by conventional methods in the art.

[0015] In the present invention, a method for preparing silicon dioxide-coated titanium dioxide is particularly provided, which specifically comprises the following steps: A1, prepare titanium dioxide into a suspension, add silicate and acid solution into the suspension, adjust the pH value, and stir and disperse at a certain temperature; A2, aging the above dispersion, adjusting the pH value to 6-8 with an acid solution, and stirring; A3, washing the product obtained in step A2, then washing with deionized water to remove the intermediate product produced during the aging process, and then distilling the obtained filtered product with alcohol to remove water to obtain silica-coated titanium dioxide.

[0016] Furthermore, the silicate in step A1 is one of sodium silicate, potassium silicate or calcium silicate; the acid solution is one of dilute sulfuric acid, dilute hydrochloric acid or dilute nitric acid; the pH value is adjusted to 8-10; the stirring temperature is 70-90°C. The mass ratio of titanium dioxide to silicate is 0.9-1.2:0.8-1.1 in terms of silicon dioxide.

[0017] Furthermore, the aging time in step A2 is 20-30 minutes; and the acid solution is one of dilute sulfuric acid, dilute hydrochloric acid or dilute nitric acid.

[0018] Furthermore, the alcohol solution described in step A3 is one of n-butanol, isobutanol or tert-butanol.

[0019] According to another aspect of the present invention, the present invention also provides a method for preparing the above-mentioned super-hydrophilic coating. The preparation of the super-hydrophilic antifouling coating is achieved by the following technical scheme: B1, under stirring, sequentially adding designed amounts of hydrophilic micron particles and hydrophilic nanoparticles into water to uniformly disperse them to obtain a dispersion; B2, slowly adding a designed amount of coupling agent to the dispersion obtained in step B1 under stirring to achieve sufficient coupling between particles; B3, add the designed amount of resin emulsion to the dispersion obtained in step B2, stir for a period of time, add the designed amount of film-forming aid, stir for a period of time, add curing agent, and then perform aging treatment to obtain a super hydrophilic antifouling coating.

[0020] Furthermore, the stirring speed in step B1 is 800-1400 r / min, the hydrophilic particles are micron-sized and nano-sized silicon dioxide and titanium dioxide or micron-sized and nano-sized silicon dioxide-coated titanium dioxide; and the concentration of the obtained dispersion is generally 0.05-0.3 g / mL.

[0021] Furthermore, in step B2, the stirring rate is 600-1200 r / min. The coupling agent is one or two of tetramethoxysilane, tetraethoxysilane and tetrapropoxysilane.

[0022] Furthermore, in step B3, the resin is a two-component epoxy or fluorocarbon resin emulsion; the stirring rate is 800-1200 r / min, and the stirring time is 20-30 min; the molecular weights of the film-forming aids carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose and hydroxypropyl cellulose are all above 100,000.

[0023] Furthermore, in step B1, when the hydrophilic micron particles and hydrophilic nanoparticles are selected from silicon dioxide and titanium dioxide, respectively, the weight ratio of silicon dioxide to titanium dioxide is 0.9-1.1:1, and the amount of micron-sized particles added is 1.2-2 times that of nano-sized particles. The size of micron-sized particles is generally 1-10 μm, and the size of nano-sized particles is generally 10-40 nm.

[0024] Furthermore, in step B3, the curing agent is a commercially available product, and the weight ratio of the added amount of the carboxymethyl cellulose to the sum of the added amounts of other celluloses is 0.9-1.1:1.

[0025] The super-hydrophilic coating provided by the present invention can obtain a super-hydrophilic coating with a micro-nano rough surface structure by simple spraying, brushing and other methods, and the preparation process is simple and suitable for large-scale production. The preparation process of the coating adopts water as the main solvent, has the characteristics of safety and environmental protection, and can be cured at room temperature. The coating is suitable for different substrate surfaces, and can be used in conjunction with other types of coatings, has good compatibility, can be used for the outer surface of the storage tank to ensure the appearance of the tank body is neat, and realizes the self-cleaning function through rainfall, especially for the coastal humid tank area, the super-hydrophilic function of the coating surface can make water droplets spread on the tank surface, block pollutants, and finally wash them away by running water, anti-fouling and dustproof.

[0026] Compared with the prior art, the present invention has the following beneficial effects: 1. Micron- and nano-scale hydrophilic particles are selected and used in a certain proportion. Particles of different sizes can be better evenly dispersed and filled in the resin to form a specific micro-nano surface structure, which effectively improves the super-hydrophilic properties of the coating.

[0027] 2. After the single-component titanium dioxide super-hydrophilic coating is removed from ultraviolet irradiation, it no longer exhibits hydrophilicity. The addition of the intrinsic hydrophilic material silicon dioxide can increase the hydrophilicity of the coating while utilizing its high specific surface area and good compatibility to effectively combine the properties of organic and inorganic. In addition, the preparation and application of silicon dioxide-coated titanium dioxide can reduce the agglomeration of titanium dioxide, inhibit the growth of titanium dioxide grains, and enhance the hydrophilicity of the coating.

[0028] 3. By adding specific silane coupling agent and cellulose, the coating has excellent dispersibility, stability and water retention. Each component forms an effective whole with good film-forming properties. Implementation

[0029] In order to make the technical problems to be solved, technical solutions and advantages of the present invention more clear, they are described in detail below in conjunction with specific embodiments.

[0030] The above scheme is further described below in conjunction with specific examples. It should be understood that these examples are used to illustrate the present invention and are not limited to the scope of the present invention. The implementation conditions adopted in the examples can be further adjusted according to the conditions of the specific manufacturer, and the unspecified implementation conditions are usually the conditions in conventional experiments.

[0031] The present invention provides a super hydrophilic antifouling coating and a preparation method thereof. The specific dosage of materials and the experimental process are shown in the following examples. Example 1

[0032] A super hydrophilic antifouling coating, comprising the following components in parts by weight: hydrophilic micro- and nanoparticles, 20 parts; Hydrophilic water-based resin, 30 parts; Coupling agent, 8 parts; Film-forming aid, 6 parts; Deionized water, 36 parts.

[0033] The hydrophilic micron and nanoparticles are micron and nanometer-sized silicon dioxide and titanium dioxide, the size of the micron-sized particles is about 1 μm, and the size of the nanometer-sized particles is about 10 nm; the titanium dioxide and silicon dioxide are 10 parts by weight each, wherein the amount of the micron-sized particles added is 1.5 times that of the nanometer-sized particles; The hydrophilic resin is a fluorocarbon resin; The coupling agent is tetramethoxysilane; The film-forming aids are carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose, and the added amount of carboxymethyl cellulose accounts for about half of the film-forming aids.

[0034] The preparation method of the super hydrophilic antifouling coating comprises the following contents: B1, add the designed amount of titanium dioxide and silicon dioxide particles to water in sequence at a stirring speed of 1000 r / min to make them uniformly dispersed to prepare a 0.1 g / mL solution; B2, slowly add the designed amount of tetramethoxysilane at a stirring speed of 800 r / min to allow sufficient coupling between the particles; B3, add the designed amount of fluorocarbon resin emulsion to the dispersion, stir at 800r / min for 30min, add the designed amount of carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose, stir for a period of time, add curing agent, mature for 2h, and obtain a super hydrophilic antifouling coating. Example 2

[0035] A super hydrophilic antifouling coating, comprising the following components in parts by weight: hydrophilic micro- and nanoparticles, 22 parts; Hydrophilic water-based resin, 33 parts; Coupling agent, 10 parts; Film-forming aid, 8 parts; Deionized water, 27 parts.

[0036] The hydrophilic micron and nanoparticles are micron and nanometer-sized silicon dioxide and titanium dioxide, with the size of the micron-sized particles being about 3 μm and the size of the nanometer-sized particles being about 20 nm; 11 parts of titanium dioxide and silicon dioxide respectively, wherein the amount of the micron-sized particles added is 1.2 times that of the nanometer-sized particles; The hydrophilic resin is epoxy resin; The coupling agent is tetramethoxysilane; The film-forming aids are carboxymethyl cellulose and hydroxyethyl cellulose.

[0037] The preparation method of the super hydrophilic antifouling coating comprises the following steps: B1, add the designed amount of titanium dioxide and silicon dioxide particles to water in sequence at a stirring speed of 1000 r / min to make them uniformly dispersed to prepare a 0.2 g / mL solution; B2, slowly add the designed amount of tetramethoxysilane at a stirring speed of 800 r / min to allow sufficient coupling between the particles; B3, add the designed amount of epoxy resin emulsion to the dispersion, stir at 1000r / min for 20min, add the designed amount of carboxymethyl cellulose and hydroxyethyl cellulose, stir for a period of time, add curing agent, mature for 2h, and obtain a super hydrophilic antifouling coating. Example 3

[0038] A super hydrophilic antifouling coating, comprising the following components in parts by weight: hydrophilic micro- and nanoparticles, 28 parts; Hydrophilic water-based resin, 32 parts; Coupling agent, 11 parts; Film-forming aid, 6 parts; Deionized water, 23 parts.

[0039] The hydrophilic micron and nanoparticles are micron and nanometer-sized silicon dioxide and titanium dioxide, with the size of micron-sized particles being about 7 μm and the size of nanometer-sized particles being about 30 nm; 14 parts of titanium dioxide and silicon dioxide respectively, wherein the amount of micron-sized particles added is 1.8 times that of nanometer-sized particles; The hydrophilic resin is a fluorocarbon resin; The coupling agent is tetramethoxysilane; The film-forming aids are carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose, and the added amount of carboxymethyl cellulose accounts for about half.

[0040] The preparation method of the super hydrophilic antifouling coating comprises the following steps: B1, add the designed amount of titanium dioxide and silicon dioxide particles to water in sequence at a stirring speed of 1000 r / min to make them uniformly dispersed to prepare a 0.2 g / mL solution; B2, slowly add the designed amount of tetramethoxysilane at a stirring speed of 800 r / min to allow sufficient coupling between the particles; B3, add the designed amount of fluorocarbon resin emulsion to the dispersion, stir at 1000r / min for 20min, add the designed amount of carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose, stir for a period of time, add curing agent, mature for 2h, and obtain a super hydrophilic antifouling coating. Example 4

[0041] A super hydrophilic antifouling coating, comprising the following components in parts by weight: hydrophilic micro- and nanoparticles, 28 parts; Hydrophilic water-based resin, 32 parts; Coupling agent, 11 parts; Film-forming aid, 6 parts; Deionized water, 23 parts.

[0042] The hydrophilic micron and nanoparticles are modified titanium dioxide coated with silicon dioxide on the surface, with a micron-grade particle size of about 1 μm and a nano-grade particle size of about 30 nm; the amount of micron-grade modified titanium dioxide added is 1.8 times that of nano-grade modified titanium dioxide; The hydrophilic resin is a fluorocarbon resin; The coupling agent is tetramethoxysilane; The film-forming aids are carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose, and the added amount of carboxymethyl cellulose accounts for about half.

[0043] The preparation method of the silicon dioxide-coated titanium dioxide comprises the following steps: A1, prepare titanium dioxide into a suspension, add sodium silicate and dilute sulfuric acid into the solution, adjust the pH value to 8-9, and stir and disperse at 80°C; A2, ripening the above solution for 30 minutes, further adjusting the pH value to 7 with dilute sulfuric acid, and stirring; A3, washing the intermediate product produced in the aging process with deionized water, and then distilling the obtained filtered product with n-butanol to remove water to obtain silica-coated titanium dioxide.

[0044] The preparation method of the super hydrophilic antifouling coating is: B1, add the designed amount of micron-sized and nano-sized titanium dioxide particles coated with silicon dioxide to water in sequence at a stirring speed of 1000 r / min to evenly disperse them to prepare a 0.15 g / mL solution; B2, slowly add the designed amount of tetramethoxysilane at a stirring speed of 800 r / min to allow sufficient coupling between the particles; B3, add the designed amount of fluorocarbon resin emulsion to the dispersion, stir at 1000r / min for 20min, add the designed amount of carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose, stir for a period of time, add curing agent, mature for 2h, and obtain a super hydrophilic antifouling coating. Example 5

[0045] A super hydrophilic antifouling coating, comprising the following components in parts by weight: hydrophilic micro- and nanoparticles, 22 parts; Hydrophilic water-based resin, 33 parts; Coupling agent, 10 parts; Film-forming aid, 8 parts; Deionized water, 27 parts.

[0046] The hydrophilic micron and nanoparticles are modified titanium dioxide coated with silicon dioxide on the surface, with a micron-sized particle size of about 9 μm and a nano-sized particle size of about 20 nm; The amount of micron-sized modified titanium dioxide added is 1.2 times that of nano-sized modified titanium dioxide; The hydrophilic resin is epoxy resin; The coupling agent is tetramethoxysilane; The film-forming aids are carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose, and the added amount of carboxymethyl cellulose accounts for about half.

[0047] The preparation method of the silicon dioxide-coated titanium dioxide is: A1, prepare titanium dioxide into a suspension, add sodium silicate and dilute sulfuric acid into the solution, adjust the pH value to 8-9, and stir and disperse at 90°C; A2, ripening the above solution for 25 minutes, further adjusting the pH value to 7 with dilute sulfuric acid, and stirring; A3, washing the intermediate product produced in the aging process with deionized water, and then distilling the obtained filtered product with n-butanol to remove water to obtain silica-coated titanium dioxide.

[0048] The preparation method of the super hydrophilic antifouling coating is: B1, add the designed amount of micron-sized and nano-sized titanium dioxide particles coated with silicon dioxide to water in sequence at a stirring speed of 1000 r / min to evenly disperse them to prepare a 0.2 g / mL solution; B2, slowly add the designed amount of tetramethoxysilane at a stirring speed of 800 r / min to allow sufficient coupling between the particles; B3, add the designed amount of epoxy resin emulsion to the dispersion, stir at 1000r / min for 20min, add the designed amount of carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl methyl cellulose, stir for a period of time, add curing agent, mature for 2h, and obtain a super hydrophilic antifouling coating. Example 6

[0049] A super hydrophilic antifouling coating, comprising the following components in parts by weight: hydrophilic micro- and nanoparticles, 20 parts; Hydrophilic water-based resin, 30 parts; Coupling agent, 8 parts; Film-forming aid, 6 parts; Deionized water, 36 parts.

[0050] The hydrophilic micron and nanoparticles are modified titanium dioxide coated with silicon dioxide on the surface, with a micron-grade particle size of about 5 μm and a nano-grade particle size of about 10 nm; the amount of micron-grade modified titanium dioxide added is 1.5 times that of nano-grade modified titanium dioxide; The hydrophilic resin is a fluorocarbon resin; The coupling agent is tetramethoxysilane; The film-forming aids are carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose, and the added amount of carboxymethyl cellulose accounts for about half.

[0051] The preparation method of the silicon dioxide-coated titanium dioxide comprises the following steps: A1, prepare titanium dioxide into a suspension, add sodium silicate and dilute sulfuric acid into the solution, adjust the pH value to 8-9, and stir and disperse at 85°C; A2, ripening the above solution for 30 minutes, further adjusting the pH value to 7 with dilute sulfuric acid, and stirring; A3, washing the intermediate product produced in the aging process with deionized water, and then distilling the obtained filtered product with n-butanol to remove water to obtain silica-coated titanium dioxide.

[0052] The preparation method of the super hydrophilic antifouling coating comprises the following steps: B1, add the designed amount of micron-sized and nano-sized titanium dioxide particles coated with silicon dioxide to water in sequence at a stirring speed of 1000 r / min to uniformly disperse them to prepare a 0.1 g / mL solution; B2, slowly add the designed amount of tetramethoxysilane at a stirring speed of 800 r / min to allow sufficient coupling between the particles; B3, add the designed amount of fluorocarbon resin emulsion to the dispersion, stir at 800r / min for 30min, add the designed amount of carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose, stir for a period of time, add curing agent, mature for 2h, and obtain a super hydrophilic antifouling coating.

[0053] Comparative Example 1: The hydrophilic micro- and nano-particles in this comparative example are only titanium dioxide and do not contain silicon dioxide. The rest is the same as in Example 1.

[0054] Comparative Example 2: In this comparative example, the hydrophilic micro- and nano-particles are only silicon dioxide and do not contain titanium dioxide. The rest is the same as in Example 1.

[0055] Comparative Example 3: The hydrophilic particles in this comparative example are all micron-sized silicon dioxide and titanium dioxide, and do not contain nano-sized particles. The rest is the same as in Example 1.

[0056] Comparative Example 4: The hydrophilic particles in this comparative example are all nanometer-sized silicon dioxide and titanium dioxide, and do not contain micrometer-sized particles. The rest is the same as in Example 1.

[0057] Comparative Example 5: The hydrophilic particles in this comparative example are micron-sized and nano-sized silicon dioxide and titanium dioxide, the amount of micron-sized particles added is 4 times that of nano-sized particles, and the rest is the same as in Example 1.

[0058] Comparative Example 6: The hydrophilic particles in this comparative example are micron-sized and nano-sized silicon dioxide and titanium dioxide, and the addition amount of the micron-sized particles is 0.5 times that of the nano-sized particles. The rest is the same as in Example 1.

[0059] Comparative Example 7: In this comparative example, the amount of micron-sized silica-coated titanium dioxide particles added is 4 times the amount of nano-sized silica-coated titanium dioxide particles added, and the rest is the same as Example 4.

[0060] Comparative Example 8: In this comparative example, the amount of micron-sized silica-coated titanium dioxide particles added is 0.5 times the amount of nano-sized silica-coated titanium dioxide particles added, and the rest is the same as Example 4.

[0061] Comparative Example 9: In this comparative example, the film-forming aid is only carboxymethyl cellulose, and the rest is the same as Example 4.

[0062] Comparative Example 10 In this comparative example, the film-forming aid is only alcohol ester 12, and the rest is the same as Example 4.

[0063] The super hydrophilic antifouling coatings prepared in the above Examples 1-6 and Comparative Examples 1-10 were tested for hydrophilicity, stain resistance and acid and alkali resistance.

[0064] Among them, the hydrophilicity is characterized by measuring the contact angle of the coating after 36 h of light exposure; The stain resistance test is carried out by brushing the prepared fly ash on the surface of the test plate coating, and then washing the fly ash coating with water for 1 minute. The cleanliness of the coating surface after washing is compared; The acid and alkali resistance of the coating was measured according to the national standard (GB / T 9274). The test results are shown in Table 1.

[0065] Table 1 Serial number Contact angle / ° Anti-fouling performance Acid and alkali resistance Example 1 7 No coal pollution residue After 72 hours of immersion, the paint film has no bubbling, discoloration, or peeling. Example 2 8.5 No coal pollution residue After 72 hours of immersion, the paint film has no bubbling, discoloration, or peeling. Example 3 7.5 No coal pollution residue After 72 hours of immersion, the paint film has no bubbling, discoloration, or peeling. Example 4 8 No coal pollution residue After 72 hours of immersion, the paint film has no bubbling, discoloration, or peeling. Example 5 9 No coal pollution residue After 72 hours of immersion, the paint film has no bubbling, discoloration, or peeling. Example 6 8 No coal pollution residue After 72 hours of immersion, the paint film has no bubbling, discoloration, or peeling. Comparative Example 1 22 A small amount of coal residue After 72 hours of immersion, the paint film has no bubbling, discoloration, or peeling. Comparative Example 2 32 Some coal pollution remains After 72 hours of immersion, the paint film has no bubbling, discoloration, or peeling. Comparative Example 3 20 A small amount of coal residue After 72 hours of immersion, the paint film has no bubbling, discoloration, or peeling. Comparative Example 4 13 There is a very small amount of coal pollution left After 72 hours of immersion, the paint film has no bubbling, discoloration, or peeling. Comparative Example 5 15 There is a very small amount of coal pollution left After 72 hours of immersion, the paint film has no bubbling, discoloration, or peeling. Comparative Example 6 14 There is a very small amount of coal pollution left After 72 hours of immersion, the paint film has no bubbling, discoloration, or peeling. Comparative Example 7 15 There is a very small amount of coal pollution left After 72 hours of immersion, the paint film has no bubbling, discoloration, or peeling. Comparative Example 8 17 There is a very small amount of coal pollution left After 72 hours of immersion, the paint film has no bubbling, discoloration, or peeling. Comparative Example 9 24 A small amount of coal residue After immersion for 48 hours, the paint film will not bubble, change color, or fall off. Comparative Example 10 25 A small amount of coal residue After immersion for 48 hours, the paint film will not bubble, change color, or fall off. From the results in Table 1, it can be seen that the super hydrophilic antifouling coating prepared by the present invention has good hydrophilicity and antifouling properties. Combined with Comparative Example 1, it can be seen that the addition of zirconium dioxide can effectively improve the hydrophilicity and antifouling properties of the coating; Combined with Comparative Example 2, it can be seen that titanium dioxide, as an important hydrophilic particle, has a great influence on the hydrophilicity and antifouling properties of the coating; Combined with Comparative Examples 3 and 4, it can be seen that the addition of nano-scale particles and micron-scale particles has a positive effect on the hydrophilicity and antifouling properties of the coating, especially the effect of nano-scale particles is more obvious; Combined with Comparative Examples 5 and 6, it can be seen that when adding titanium dioxide and silicon dioxide, appropriate micron-scale and nano-scale particles can effectively improve the hydrophilicity and antifouling properties of the coating. The ratio has a positive effect on improving the hydrophilicity and stain resistance of the coating; from Comparative Examples 7 and 8, it can be seen that when adding silica-coated titanium dioxide particles, the appropriate ratio of micron-scale and nano-scale particles also has a positive effect on improving the hydrophilicity and stain resistance of the coating; from Comparative Example 9, it can be seen that the addition of comprehensive and appropriate cellulose has a positive effect on the hydrophilicity, stain resistance and acid and alkali resistance of the coating; from Comparative Example 10, it can be seen that only using conventional film-forming aids, the hydrophilicity, stain resistance and acid and alkali resistance of the coating are all reduced. Comprehensively from the comparative examples, it can be seen that the changes in the type, size and amount of hydrophilic particles added in the coating have little effect on the acid and alkali resistance of the coating, but have a significant effect on the hydrophilicity and stain resistance of the coating.

[0066] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. For ordinary technicians in this technical field, several improvements can be made without departing from the principles of the present invention. These improvements should also be regarded as within the scope of protection of the present invention.

Claims

1. A super hydrophilic antifouling coating, characterized in that: The following components are included in parts by weight: Hydrophilic micron particles and hydrophilic nanoparticles, 15-30 parts; Hydrophilic resin, 20-40 parts; Coupling agent, 5-15 parts; Film-forming aid, 1-8 parts; Deionized water, 20-50 parts; The hydrophilic micron particles include silicon dioxide and titanium dioxide particles, and the hydrophilic nanoparticles include nano-scale silicon dioxide and titanium dioxide particles; or the hydrophilic micron particles and hydrophilic nanoparticles are selected from silicon dioxide-coated titanium dioxide particles.

2. The super hydrophilic antifouling coating according to claim 1, characterized in that: The particle size of the micron-sized particles is 1-10 μm, and the particle size of the nano-sized particles is 10-40 nm.

3. The super hydrophilic antifouling coating according to claim 1, characterized in that: The weight ratio of the hydrophilic micron particles to the hydrophilic nanoparticles is 1.2-2:

1.

4. The super hydrophilic antifouling coating according to claim 1, characterized in that: The hydrophilic resin is epoxy resin or fluorocarbon resin.

5. The super hydrophilic antifouling coating according to claim 1, characterized in that: The coupling agent is one or more of tetramethoxysilane, tetraethoxysilane and tetrapropoxysilane.

6. The super hydrophilic antifouling coating according to claim 1, characterized in that: The film-forming aid is one or more of carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose and hydroxypropyl methyl cellulose, and the molecular weight of the film-forming aid is above 100,000.

7. The super hydrophilic antifouling coating according to claim 6, characterized in that: The film-forming aid is selected from carboxymethyl cellulose and a combination of one or more of hydroxyethyl cellulose, hydroxypropyl cellulose and hydroxypropyl methyl cellulose.

8. The super hydrophilic antifouling coating according to claim 1, characterized in that: When both the micron particles and the nanoparticles are titanium dioxide and silicon dioxide, the total added amount weight ratio of titanium dioxide and silicon dioxide is 0.9-1.1:

1.

9. The super hydrophilic antifouling coating according to claim 1, characterized in that: The method for preparing silicon dioxide-coated titanium dioxide comprises the following steps: A1, prepare titanium dioxide into a suspension, add silicate and acid solution into the suspension, adjust the pH value, and stir to disperse; A2, aging the above dispersion, adjusting the pH value to 6-8 with an acid solution, and stirring; A3, washing the product obtained in step A2, then washing with deionized water to remove the intermediate product produced during the aging process, and then distilling the obtained filtered product with alcohol to remove water to obtain silica-coated titanium dioxide.

10. The super hydrophilic antifouling coating according to claim 9, characterized in that: The silicate is one of sodium silicate, potassium silicate or calcium silicate; the acid solution is one of dilute sulfuric acid, dilute hydrochloric acid or dilute nitric acid.

11. The super hydrophilic antifouling coating according to claim 9, characterized in that: In step A1, the pH value is adjusted to 8-10.

12. The super hydrophilic antifouling coating according to claim 9, characterized in that: The stirring and dispersing temperature is 70-90°C.

13. The super hydrophilic antifouling coating according to claim 9, characterized in that: The mass ratio of titanium dioxide to silicate is 0.9-1.2:0.8-1.1 based on silicon dioxide.

14. The super hydrophilic antifouling coating according to claim 1, characterized in that: The aging time in step A2 is 20-30 minutes.

15. The super hydrophilic antifouling coating according to claim 1, characterized in that: The alcohol solution described in step A3 is one of n-butanol, isobutanol or tert-butanol.

16. The method for preparing the super hydrophilic coating according to any one of claims 1 to 15, characterized in that: The following steps are involved: B1, under stirring, sequentially adding designed amounts of hydrophilic micron particles and hydrophilic nanoparticles into water to uniformly disperse them to obtain a dispersion; B2, slowly adding a designed amount of coupling agent to the dispersion obtained in step B1 under stirring to achieve sufficient coupling between particles; B3, add the designed amount of resin emulsion to the dispersion obtained in step B2, stir for a period of time, add the designed amount of film-forming aid, stir for a period of time, add curing agent, and then perform aging treatment to obtain a super hydrophilic antifouling coating.

17. The preparation method according to claim 16, characterized in that: The concentration of the dispersion obtained in step B1 is 0.05-0.3 g / mL.

Citation Information

Patent Citations

  • Aqueous anticorrosive heat-insulation paint and preparation method

    CN103819989A

  • Modified nano titanium dioxide self-cleaning coating and preparation method thereof

    CN106380981A

  • Superhydrophilic coating material and preparation method thereof, prepared superhydrophilic coating and application thereof

    CN109825156A

  • Super-hydrophilic self-cleaning coating material composition and preparation method thereof, and super-hydrophilic self-cleaning glass and preparation method thereof

    CN110093050A

  • Hydrophobic coating and preparation method thereof

    CN108384036A